Orthodontic and orthopedic rehabilitation of adult patients with congenital cleft lip and palate (clinical case) - L.B. Halych; V.D. Kuroyedova; N.V. Tsvetkova; L.V. Halych (Medičnì Perspektivi, 2024)
Congenital cleft lip, alveolar process, hard and soft palate are common anomalies of the development of human organs and in terms of frequency occupy one of the first places among other defects of the human body. The clinical study and treatment of cleft lip and palate, malocclusions that accompany this defect have always been of great interest in orthodontics and orthopedic dentistry. This is due to the fact that malocclusions in this group of patients are complex and difficult to treat, as morphological changes are combined with significant functional disorders. The aim of the work was to demonstrate a clinical case of orthodontic and orthopedic rehabilitation of patients with congenital bilateral cleft lip and palate after cheilouranoplasty. A clinical case of a complex treatment of a 25-year-old female patient with bilateral cleft lip, alveolar process, hard and soft palate after cheilouranoplasty performed in childhood is presented. During the clinical examination, an irregular shape of the upper dentition was established due to its sharp narrowing and alveolar shortening in the area of canines and first premolars. A deep reverse bite was formed, a false progeny with a sagittal fissure of up to 10 mm, bilateral vestibular crossbite, contact on the first and second molars of the upper and lower jaws was observed, adentia 12, 22, 23. With a sharp narrowing of the upper dentition at the first stage of orthodontic treatment, Nord's apparatus was used. At the second stage, the brace technique was applied, namely, the straight arch technique. After expanding, lengthening the upper dentition, creating space for missing teeth, reducing the size of the lower dentition by removing 34, 44, the patient continued treatment at the orthopedic department. At an appointment with an orthopedic dentist, after an objective and subjective examination, according to Kennedy the patient was diagnosed as III class, I subclass of the upper jaw. Defects of the alveolar process of the upper jaw, formed as a result of adentia, connection of the oral cavity with the nasal cavity in places of non-union of the alveolar process were established. In this clinical situation, the manufacturing of a complete esthetic-cosmetic structure, namely a metal-ceramic dental bridge with obturating parts is indicated. Thus, the demonstrated clinical case can be considered as one of the methods of a complex orthodontic and orthopedic rehabilitation of adult patients with congenital cleft lip, alveolar process and palate.